Judi Online Dalam Perspektif Hukum Islam Dan Undang-Undang Di Indonesia - Fajri bahiyah dienny; Ritonga, Irwan; Yansah Munthe , Ruly; Apriza Bay , Wahyu; Marbun , Sahat (Tabayyun : Journal Of Islamic Studies, 2025)
Online gambling has become a rapidly growing social issue in the digital era. From the perspective of Islamic law, gambling is categorized as a prohibited act (haram) because it contains elements of maysir (gambling), which contradicts the values of justice, honesty, and lawful effort. This prohibition is emphasized in the Qur'an, such as in Surah Al-Baqarah (2:219) and Al-Maidah (5:90-91), which describe gambling as an act that brings great sin and corrupts societal morals. Meanwhile, under Indonesia's positive law, gambling, including online gambling, is also considered an illegal act. This is regulated in Articles 303 and 303 bis of the Indonesian Criminal Code (KUHP). Furthermore, online gambling is specifically prohibited under Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law). The law explicitly bans all forms of gambling activities using information technology, with criminal sanctions in the form of imprisonment or fines for offenders.